Does Fleet Street shape politics? Estimating the Effect of Newspaper Coverage about Globalization on the Support for Unemployment Insurance - Benjamin Protte (University of Mannheim, Department of Economics, 2012)
In this paper, I quantify the role of media in the formation of support for unemployment insurance. Theory suggests that individuals who feel threatened by globalization demand compensatory policies. Using a novel method of quantitative text analysis, I derive measures on the stance to globalization for all major British newspapers between 2001 and 2005. Results of regressing individual demand for unemployment insurance on my measure of globalization-specific newspaper positions show a consistent, sizable, and significant effect. This effect is in line with theoretical predictions and is robust to the inclusion of various controls such as trade effects and to accounting for biases resulting from self-selection of readers into newspapers with similar policy attitudes.
urn:nbn:de:bsz:180-madoc-325552
Keywords: F15; H11; H55; L82; D78; 330; Globalization; Compensation Hypothesis; Welfare State; Media; Quantitative Text Analysis